2006
DOI: 10.1246/bcsj.79.373
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Double-Proton Transfer in the 7-Azaindole Dimer in the Gas Phase. Resolution of the Stepwise versus Concerted Mechanism Controversy and a New Paradigm

Abstract: The 7-azaindole dimer (7AI 2 ) is a prototype of double hydrogen-bonded molecules. 7AI 2 has been considered as a model DNA base pair and has attracted much attention to the mechanism of the excited-state double-proton transfer (ESDPT). Two ESDPT mechanisms, stepwise and concerted mechanisms, have been proposed so far. Great efforts have been devoted to clarify the mechanism of ESDPT using experimental and theoretical methods. However, the reaction mechanism had been controversial for more than a decade. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…The doubly hydrogen-bonded dimer of 7-azaindole is a prototypical system showing such a reaction in the photoexcited state. This dimer has served as one of the most central model systems, and hence its photochemistry and photophysics have been extensively studied for more than three decades (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Spectroscopic measurements revealed that the 7-azaindole dimer exhibits a double proton transfer reaction after photoexcitation ( Fig.…”
mentioning
confidence: 99%
“…The doubly hydrogen-bonded dimer of 7-azaindole is a prototypical system showing such a reaction in the photoexcited state. This dimer has served as one of the most central model systems, and hence its photochemistry and photophysics have been extensively studied for more than three decades (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Spectroscopic measurements revealed that the 7-azaindole dimer exhibits a double proton transfer reaction after photoexcitation ( Fig.…”
mentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 24 The profiles of the  ND bands of these dimers exhibit a relatively simple pattern similar to those of the  ND bands of the deuterated normal dimers shown in Figure 11, however, the bandwidths of the former are much wider than those of the normal dimer. As described in Section III-1, the activation energy barrier of the PTR determined is about 2300 cm -1 , which is close to the excitation energy of the  ND mode.…”
Section: Iii-3 Ir Spectroscopy Of the 7-ai Tautomeric Dimermentioning
confidence: 75%
“…After these studies, several research groups argued on the mechanism of PTR for more than 6 years. Details of the debates were reviewed by Sakota and Sekiya [24]. Here, we briefly summarize these studies and the kinetic mechanism of the PTR reaction of (7-AI) 2 both in solution and in the gas phase.…”
Section: Ii-2 Spectroscopy Of 1-ac Monomer and Its Dimermentioning
confidence: 98%
See 1 more Smart Citation
“…1H‐pyrrolo[3,2‐ h ]quinoline ( 10 ), a bifunctional HB donor‐acceptor molecule, has been investigated in a series of papers 36–45 as a chromophore complementary to 7‐azaindole (7AI). The latter has become a paradigm for excited‐state double‐proton transfer, 46–58 the reaction occurring rapidly in 7AI dimers and much more slowly in complexes with alcohols and water. Both 10 and 7AI are characterized by the presence of the same structural motifs (), the NH proton donor and the pyridine‐type nitrogen acceptor.…”
Section: Resultsmentioning
confidence: 99%